Human right-based approach to disaster risk management (2018)
Since the beginning of the 21st century, there has been an increasing trend of disasters caused by natural hazards such as earthquake, tsunami, hurricane, flood etc., and trends in climate change show increasing vulnerability and exposure of people to such disasters. Disasters have huge economic, environmental and social impacts ranging from loss of life, injury, disease displacement and other negative effects on human, physical, mental and social wellbeing, to damage to property, destruction of assets, loss of services, social and economic disruption, and environmental degradation. While disasters predispose victims (especially vulnerable groups such as children, women and persons with disabilities) to human rights violations emanating from disaster impacts, disaster risk management requires a holistic approach which integrates the rights of victims. Disaster risk management encompasses a systematic process of implementing strategies for preparing, responding and recovery from disaster in order to lessen the adverse impacts of hazard and reduce the possibility of disaster. Thus, human rights protection forms an important part of disaster risk management. The United Nations presupposes that human rights principles should guide disaster risk management, ranging from pre-disaster mitigation and preparedness measures to emergency relief and rehabilitation efforts. Even though there are a number of international soft law instruments concerning the rights of victims in disaster and State obligations in disaster prevention and management activities, the operational context of these rules should be explored in order to ensure an effective disaster risk management regime. Human rights may also provide appropriate mechanisms for compensation for preventable disaster losses. This article considers the subject of disaster risk management from a human rights perspective.